Sal Si Puedes (Escape If You Can): Cesar Chavez and the New American Revolution - PETER MATTHIESSEN (University of California Press, 2014)
"ThE rich have money-and the poor have time." Those were the words of Cesar Chavez in 1991, two years before his death. Is it sheer fancy to suggest that this sentence alone summarizes the dominant concerns of his life? Chavez's life was defined by patience. Patience was his weapon against the grape owners and the Teamsters, against the abuse of the downcast. He had plenty of patience, much more than a normal person, and it was proven in his nonviolent marches, fasts, and petitions. "We don't have to win this year or next year or even the year after that," he told his followers. 'We'll just keep plugging away, day after day.... We will never give up. We have nothing else to do with our lives except to continue in this nonviolent fight." Of course, there is such a thing as too much patience. How long will it take for Chavez's message to penetrate the American psyche? He's been dead for almost a decade. His name and face adorn schools and public parks. He pops up in advertisements for Macintosh computers, along with John Lennon and the Dalai Lama-"Think Different"! But these ghostlike appearances are empty of all ideological significance: it's a tame Chavez, not the quixotic knight he was; a brand name, as disposable as any celebrity in Hollywood. My generation is too young to have witnessed Chavez's odyssey from obSCUrity to legend. My appreciation for his courage and forbearance came indirectly. I learned about him from books and documentaries. Every reference to him was cloaked in an aura of sanctity. But as with most saints, it was hard to figure out exactly what he had done on the road to beatitude. No doubt Chavez was the most important Hispanic American political figure of the twentieth century. But for someone like me, born at the apex of his career, outside the United States, it was almost impossible to lift him from the junk box where icons are stored away and reinsert him into history. Somehow Chavez the man had become Chavez the statue: pigeons sat motionless on his nose and hands, his beautiful bronze skin corroded by the passing of time.